The Principal's Role as Supervisor to Develop Pedagogic Competence of the Elementary School’s Teacher - Dea Mustika; Nurhayati; Zulhendri; Rusdinal; Nurhizrah Gistituati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the role of school principals in the development of teacher pedagogic competencies in elementary schools. For the development of teacher pedagogic competence, this research refers to the academic supervision of teachers. This study used descriptive qualitative method. Data collection techniques through observation, interviews and documentation review. Testing the validity of the data using source triangulation and technical triangulation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The conclusion of this study is that the principal acts as a supervisor in the development of teacher pedagogical competencies through the implementation of activities to review learning tools, monitor learning tools and choose supervision assessment instruments.